2022
DOI: 10.2147/dmso.s377072
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Adipokines and IL-10 in Association with Anthropometry in Prediction of Insulin Resistance in Obese Children

Abstract: This is a case-controlled study, with two hundred children enrolled. They were divided into an obese group of 100 children who had BMI ≥ 95th percentile according to CDC criteria and a group of 100 children with normal weight. All enrolled children were subjected to detailed medical history and clinical examination, in addition to measuring fasting blood sugar, fasting serum insulin, HOMA-IR calculation, lipid profile analysis, total serum cholesterol, low-and high-density lipoproteins (LDL and HDL), and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This obesity-induced dyslipidemia in children has been documented in numerous studies worldwide, including in Slovenia, Portugal, Iran, Argentina, Egypt, Brazil, Turkey, Italy, and India. [ 22 24 25 ] The observations from the current study further corroborate these findings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This obesity-induced dyslipidemia in children has been documented in numerous studies worldwide, including in Slovenia, Portugal, Iran, Argentina, Egypt, Brazil, Turkey, Italy, and India. [ 22 24 25 ] The observations from the current study further corroborate these findings.…”
Section: Discussionsupporting
confidence: 86%
“…that demonstrate a compensatory decrease in ghrelin when adipose tissue increases, this study reveals increased ghrelin levels in obese children. [ 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ] This discrepancy suggests that the potential negative feedback mechanism to regulate energy consumption may not be present, as the lower concentration of ghrelin observed in obese children challenges the expected pattern. [ 40 ] Instead, these findings align with the studies that show a significant elevation in ghrelin levels among the obese groups.…”
Section: Discussionmentioning
confidence: 99%
“… 37 However, it has also been reported that serum adipsin had no association with insulin resistance in obese children. 38 A positive correlation between adipsin and HOMA-IR was observed in our study. We found that the more severe the MAFLD in patients, the higher the adipsin levels.…”
Section: Discussionsupporting
confidence: 74%
“…These facts could help us to understand the results found in rodents. Serum and urinary levels of LCN-2 are associated with the markers of obesity, insulin resistance and diabetes both in adults and adolescents [ 44 , 45 , 46 ]. It was reported that circulating levels of LCN-2 was markedly increased in subjects that had impaired fasting glucose and glucose tolerance compared to normal subjects.…”
Section: Role Of Novel Adipokines In Non-diabetic Obesitymentioning
confidence: 99%